Antitumor Research on Artemisinin and Its Bioactive Derivatives - Yunqin Zhang; Guowei Xu; Shuqun Zhang; Dong Wang; P. Saravana Prabha; Zhili Zuo (Natural Products and Bioprospecting, 2018)
Abstract Cancer is the leading cause of human death which seriously threatens human life. The antimalarial drug artemisinin and its derivatives have been discovered with considerable anticancer properties. Simultaneously, a variety of target-selective artemisinin-related compounds with high efficiency have been discovered. Many researches indicated that artemisinin-related compounds have cytotoxic effects against a variety of cancer cells through pleiotropic effects, including inhibiting the proliferation of tumor cells, promoting apoptosis, inducing cell cycle arrest, disrupting cancer invasion and metastasis, preventing angiogenesis, mediating the tumor-related signaling pathways, and regulating tumor microenvironment. More importantly, artemisinins demonstrated minor side effects to normal cells and manifested the ability to overcome multidrug-resistance which is widely observed in cancer patients. Therefore, we concentrated on the new advances and development of artemisinin and its derivatives as potential antitumor agents in recent 5 years. It is our hope that this review could be helpful for further exploration of novel artemisinin-related antitumor agents. Graphical Abstract